2015
DOI: 10.1097/hjh.0000000000000612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of birth weight on life-course blood pressure levels among children born premature

Abstract: These longitudinal data suggest that elevated BP levels associated with prematurity are more likely to be present in those with fetal growth restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 29 publications
1
53
1
2
Order By: Relevance
“…Our studies, however, are aligned with the recent large longitudinal study (n = 1756), where preterm AGA and preterm FGR were separated. 44 In this study, although there were no differences identified in blood pressure between 3 and 18 years of age, higher blood pressure was identified between 34 and 49 years of age. 44 It is possible in the group of children we studied, that blood pressure differences caused by either preterm birth or FGR or the combination of both may emerge later in life, which may make this age group an ideal window to target preventive care for cardiovascular risk, if indeed this group goes on to have higher blood pressure later in life.…”
Section: Baseline Blood Pressure and Heart Rate During Sleepcontrasting
confidence: 60%
“…Our studies, however, are aligned with the recent large longitudinal study (n = 1756), where preterm AGA and preterm FGR were separated. 44 In this study, although there were no differences identified in blood pressure between 3 and 18 years of age, higher blood pressure was identified between 34 and 49 years of age. 44 It is possible in the group of children we studied, that blood pressure differences caused by either preterm birth or FGR or the combination of both may emerge later in life, which may make this age group an ideal window to target preventive care for cardiovascular risk, if indeed this group goes on to have higher blood pressure later in life.…”
Section: Baseline Blood Pressure and Heart Rate During Sleepcontrasting
confidence: 60%
“…One consistent observation was that adults born preterm had significantly higher systolic and diastolic blood pressure values, ranging between 2 and 8 mmHg, compared to their age‐matched term controls . A significantly higher prevalence of hypertension was also reported in one study , but this finding was not consistent. A report from the Adults Born Preterm International Coalition provided precise estimates of blood pressure changes.…”
Section: System/organ‐specific Outcomesmentioning
confidence: 87%
“…In 9 of 126 reports, SGA cohorts were included , and in two others, IUGR cohorts were included . These reports also contained outcomes for adults born preterm who were not SGA.…”
Section: System/organ‐specific Outcomesmentioning
confidence: 99%
“…Our data could not confirm that being small for gestational age at birth is a perinatal risk factor for high BP in children born extremely preterm. Over a life‐course perspective, being born small for gestational age has been considered to be more harmful in terms of risk of hypertension than preterm birth . However, life‐course studies of historic perinatal cohorts may be biased by selective survival among those born preterm and do not contain today's survivors born after extremely short gestations.…”
Section: Discussionmentioning
confidence: 99%